2018
DOI: 10.1159/000488209
|View full text |Cite
|
Sign up to set email alerts
|

Does the Duration of Fixed Orthodontic Treatment Affect Caries Activity among Adolescents and Young Adults?

Abstract: This cross-sectional study assessed the relationship between fixed orthodontic treatment duration and caries activity. Two hundred and sixty 10- to 30-year-olds were divided into 4 groups (n = 65): no fixed orthodontic appliances (G0), orthodontic treatment for 1 year (G1), 2 years (G2), or 3 years (G3). Orthodontic treatment duration was significantly associated with active caries: prevalence was 1.5% for G0, 27.7% for G1, and 72.3% for G2 and G3; the median number of lesions was 0 for G0 and G1 and 2 for G2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 11 publications
0
29
0
3
Order By: Relevance
“…A previous cross-sectional study by our research group investigated caries activity among orthodontic patients using clinical examinations taken after tooth cleaning and drying. 13 The authors showed that the longer the duration of the orthodontic treatment, the higher the prevalence/extent of active caries lesions. However, only longitudinal studies may provide evidence of causality due to the temporal component.…”
Section: Introductionmentioning
confidence: 99%
“…A previous cross-sectional study by our research group investigated caries activity among orthodontic patients using clinical examinations taken after tooth cleaning and drying. 13 The authors showed that the longer the duration of the orthodontic treatment, the higher the prevalence/extent of active caries lesions. However, only longitudinal studies may provide evidence of causality due to the temporal component.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, patients ongoing long treatment are more exposed to the potential accidents and complications inherent to orthodontics. It has been reported that longer orthodontic treatments have a negative impact on patients' attitude, especially when it comes to the maintenance of periodontal health (ALHAIJA et al, 2018) and the occurrence of caries (PINTO et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Ini adalah kasus resorpsi akar, bintik-bintik putih, lesi karies, dan peradangan gingiva. [29] Tabel 5.1.2 mengenai derajat diskolorisasi gigi menunjukkan berada pada derajat diskolorisasi 1 dimana 0,01%-25% daerah yang terdapat diskolorisasi. Hasil ini sejalan dengan Penelitian Amalia (2009) menyebutkan bahwa tingkat pengetahuan pasien tentang perawatan ortodonti cekat masuk dalam kategori pengetahuan rendah.…”
Section: Pendahuluanunclassified